Pola Kerjasama Pemerintah Kabupaten Banyuwangi Dengan PT. Pelindo dalam Pengelolaan Wisata Green Watu Dodol Banyuwangi - Sedarmayanti; Sri Kamariyah (STIEPAR YAPARI Bandung, 2020)
Ketapang is one of the villages that have abundant natural resources, but the human resources are still insufficient to enhance the existing tourism potential. The purpose of this research is to analyze comprehensively about Banyuwangi Regency Work Pattern with PT. Pelindo in managing Green Watu Dodol Tourism Object in Ketapang village, Banyuwangi regency, and also give suggestion or suggestion for optimal activity.This method of research is also a way of solving problems that must be done for scientific data and also as a means of seeking the truth with the steps that following existing provisions. In the process of printing, this scientific paper will be used the methods used as a guide in conducting research steps.The results of the research indicate that the authority of the Regional Government based on Article 12 paragraph (3) letter b Law no. 23 of 2014 on Regional Government, precisely the jurisdiction of the District Government in Article 30 of Law no. 10 the Year 2009 on Tourism. A lokal government with its authority may regulate, control, control and protect the community as well as natural resources and natural resources. The development of tourism is strived to be developed with the approach of growth and equity of the economy for the welfare of society and development oriented to the development of the region, relying on the community, and the nature of community members covering various aspects including business management cooperation. The government should be able to position development in existing development di Watu Dodol.